Cultural studies and cultural industries in northeast Asia : what a difference a region makes - Berry, Chris, 1959 April 28-; Liscutin, Nicola; Mackintosh, Jonathan D. (TransAsia--screen cultures., 2009)
Highlights how regional popular cultures and creative industries have become globally powerful, analyzing gender and labor issues amid differing regulatory frameworks of cultural production and piracy in Asia.